Hippocampal miR-211-5p regulates neurogenesis and depression-like behaviors in the rat. (15th August 2021) - Li, Ye; Fan, Cuiqin; Gao, Rui; Lan, Tian; Wang, Wenjing; Yu, Shu Yan
Abstract: Emerging evidence has shown that microRNAs (miRNAs) contribute to the pathogenesis of depression, a potentially life-threatening and disabling mental disorder caused by the interaction of genetic and environmental factors. However, the specific miRNAs and their underlying molecular mechanisms as involved in the pathogenesis and development of depression remain largely unknown. In the present study, we screened miRNA expression profiles and found that miR-211-5p was significantly down-regulated within the dentate gyrus (DG) hippocampus in the chronic unpredictable mild stress (CUMS) induced rat model of depression. Deficits in miR-211-5p were accompanied with reductions in neurogenesis and increased apoptosis in these CUMS rats. In contrast, an up-regulation of miR-211-5p within the DG area in CUMS rats promoted neuronal neurogenesis, reduced neuronal apoptosis via suppression of the Dyrk1A/STAT3 signaling pathway and relieved depression-like behaviors in these CUMS rats. In rats subjected to a knock-down of miR-211-5p in the DG there was an increase in neuronal apoptosis and a decrease in neuronal regeneration, effects which were accompanied with an induction of depression-like behaviors. Taken together, the results of our study reveal that altered levels of miR-211-5p in the hippocampal DG area exert a significant impact on neurogenesis, apoptosis and thus depression-like behaviors in rats. These findings suggest that the miR-211-5p/Dyrk1A pathway plays an important role in the pathogenesis of depression and may serve as a potential therapeutic target for the treatment of depression. Graphical abstract: Image 1 Highlights: CUMS induced depression-like behavior accompanied with neuronal anomalies within hippocampal DG region. MiR-211-5p was down-regulated within DG region in CUMS-induced depression model. Up-regulating miR-211-5p ameliorate the neural apoptosis within DG region in depression model. MiR-211-5p rescues neuronal anomalies by targeting Dyrk1A/STAT3/p53/ID2 pathway within DG.